If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5 = 25 + -2x Reorder the terms: 5 + 4x = 25 + -2x Solving 5 + 4x = 25 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 5 + 4x + 2x = 25 + -2x + 2x Combine like terms: 4x + 2x = 6x 5 + 6x = 25 + -2x + 2x Combine like terms: -2x + 2x = 0 5 + 6x = 25 + 0 5 + 6x = 25 Add '-5' to each side of the equation. 5 + -5 + 6x = 25 + -5 Combine like terms: 5 + -5 = 0 0 + 6x = 25 + -5 6x = 25 + -5 Combine like terms: 25 + -5 = 20 6x = 20 Divide each side by '6'. x = 3.333333333 Simplifying x = 3.333333333
| 50x=15+9 | | (4x+5y)*(3x-6y)= | | 3x+7=9x-1 | | 0=3x^2+x-5.5 | | -16x=-12 | | 18x-9(3x+5)=0 | | 4x^2-49x=80 | | 4x^2-49=80 | | 3y-13=53 | | 2=4-2b | | 13=3k-2 | | x=50+9 | | 6x-7=5x(x+3) | | 25x^2-16x+5=0 | | 25x^2-16x=5 | | k+(16)=2 | | 15x+9=50 | | 15+3=22 | | X+1=-3X+4 | | 3k+6=0 | | 28+x=28+x-14 | | 10.4x-6=34 | | 17=5z+2 | | 4x-3=-10x+4 | | 2x^2-3kx+5k=0 | | (4x+2)+(2-3x)=4x-(3-x)+4 | | 0=1x^2-9x+20 | | 3x+1=12x-8 | | 1*8=x | | 4k^2+9=0 | | 0=2x^2-18*x+40 | | kx^2-10x+5=y |